Gambaran Pengetahuan Pembersihan Gigi Tiruan Sebagian Lepasan Akrilik di Manado - Preizy Keszia Shelomita Hidayat; Andy Wirahadikusumah (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Tooth loss can interfere mastication, phonetics, aesthetics use, even social relationship of an individual. Knowledge plays an important role in humans acting as a person cleans the dentures. A person’s level of knowledge on dental and oral health is lined proportional to a person’s level of health. According to the 2018 RISKESDAS in the city of Manado, there is a gap difference of toothe loss and the use of dentures. RSUP Prof. Dr. R. D. Kandou is a type A hospital, as a reference for manufacture of dentures. Goals: The aim of this study is to determine the knowledge level of denture users regarding the cleaning of acrylic removable partial dentures at Prof. Dr. R. D. Kandou. Methodology: This is a descriptive observational study with a cross-sectional research design. The study was conducted by distributing questionnaires consisting 10 questions related to knowledge of the patients in the Dental Polyclinic at Prof. RSUP. Dr. R.D. Kandou. Result: The results showed that 59.2% of the 98 respondents participated in this study had a good knowledge. Respondents with middle age have better knowledge than the elderly and the old. Female respondents are better in knowledge than males. The majority of respondents with a final undergraduate education level have a good level of knowledge. All respondents have been given instructions from the dentist. Conclusion: In general, the knowledge of the Dental Polyclinic patient at Prof. RSUP. Dr. R. D. Kandou, Manado is quite good at cleaning acrylic removable partial dentures.